DOSE AND IMBIBITION TIMES OF HYDROGEN PEROXIDE IN GERMINATION AND INITIAL GROWTH OF COTTON (Gossypium barbadense L.)] - Arturo Morales Pizarro; Doris Rondoy-Castro; Pierina Escobedo-Huancas; Esther Durante-Montejo; Angie Veramatus-Mendoza; Jonathan Juárez-Vílchez; Henry Morocho-Romero; Roger Chanduvi-García; Marcos Quiroz-Calderón; Mariano Calero-Merino; Ricardo Peña-Castillo (Tropical and Subtropical Agroecosystems)
Background: Cotton is a crop of great socioeconomic interest in the textile industry in Peru, however, it is sown directly in the field where it presents irregular germination. Objective: To evaluate the effect of four doses of hydrogen peroxide and two imbibition times on the germination and initial growth of cotton. Methodology: The commercial hydrogen peroxide CP (H2O2 at a concentration of 3 g 100 mL-1) was used in the treatments: T0 (control- distilled water), T1 (10% CP), T2 (30% CP), T3 (50% CP), T4 (100% CP) subjected to 6 and 12 h of imbibition. Germination evaluations were made: germination percentage (GP), germination speed (GS), germination index (GI), Biometry: seed weight (SW), stem length (ST), number of leaves (NL) and root length (RL). Stem biomass: fresh weight (SFW) and dry weight (SDW), and root biomass: fresh weight (RFW) and dry weight (RDW). Results: T3-6 h improved germination variables. T1-6 h improved biometry and biomass variables. SW presented a negative correlation with NL. NL was positively correlated with SDW. SDW was positively correlated with SFW. Also, SFW with RL, RDW and RFW. RL with RDW. RDW with RFW and ST. The RFW with ST. Implications: The use of H2O2 increases germination and biomass of cotton seedlings. Conclusion: T3-6 h improved germination variables. However, T1-6 h improved biometry and biomass variables.